2015
DOI: 10.1016/j.proeng.2015.08.732
|View full text |Cite
|
Sign up to set email alerts
|

All-Quartz High Accuracy MEMS Pressure Sensor Based on Double-Ended Tuning Fork Resonator

Abstract: This paper reports an all-quartz high accuracy MEMS absolute pressure sensor based on high Q double-ended tuning fork (DETF) resonator, which is suitable for application in automotive, petroleum, meteorological, aerospace and spacecraft field. etc. The main parts of the MEMS pressure sensor, including the DETF resonator, diaphragm and back cavity structure, are all fabricated by quartz crystal using MEMS process. These pieces are bonded together as 'sandwich' structure to form the absolute pressure sensing uni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(4 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…While there are many types of quartz resonant devices, most quartz sensors, such as accelerometers and pressure sensors, use double-ended tuning forks or double-clamped single beams 41 , 42 ; as such, we have applied those designs in this fabrication experiment. Examples of the quartz shapes as fabricated by our FLICE process are presented in Figs.…”
Section: Methodsmentioning
confidence: 99%
“…While there are many types of quartz resonant devices, most quartz sensors, such as accelerometers and pressure sensors, use double-ended tuning forks or double-clamped single beams 41 , 42 ; as such, we have applied those designs in this fabrication experiment. Examples of the quartz shapes as fabricated by our FLICE process are presented in Figs.…”
Section: Methodsmentioning
confidence: 99%
“…However, these methods have their own drawbacks in the compensation processes. Wang, J. et al reported a resonant pressure sensor that employs a temperature sensor for temperature compensation [19,20]. This method is only suitable for a slowly varying temperature.…”
Section: Introductionmentioning
confidence: 99%
“…Resonant pressure sensors became the most attractive candidates for high-precision pressure measurements. A variety of structures and fabrication processes were proposed to improve the performance of resonant pressure sensors, including the quality factor, sensitivity, and so on, but few resonant pressure sensors have been successfully commercialized [4][5][6][7][14][15][16][17][18][19][20][21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%